Effect of occupation on sleep duration among daytime Japanese workers: A cross-sectional study. Issue 49 (10th December 2021) - Kakamu, Takeyasu; Hidaka, Tomoo; Masuishi, Yusuke; Kasuga, Hideaki; Endo, Shota; Sakurazawa, Midori; Munakata, Yukari; Tajimi, Kimitaka; Fukushima, Tetsuhito
Abstract : Abstract: Occupation is one of the factors contributing to the loss of sleep. Although many studies have investigated sleep loss due to irregular and nighttime shifts, the causes of sleep loss in daytime workers remain unknown. The aims of the present study were to determine whether occupation is a dependent factor for sleep duration and whether working status and lifestyle are related to sleep duration. We examined the health check results of 17, 519 (9028 men and 8491 women) workers who had at least 1 health check between the fiscal years 2013 and 2019. We asked about the workers' occupation, bedtime, dinner time, overtime work, and commuting time, using a self-administered questionnaire at their health check. The occupations were classified into 4 categories: high white-collar, low white-collar, pink-collar, and blue-collar. We conducted a linear regression model and analysis of covariance to investigate the effect of occupation on sleep duration. As a result of linear regression analysis, bedtime, overtime work and occupation were significantly associated with decreased sleep duration in males, and bedtime, age, and occupation were significantly associated with decreased sleep duration in females. Analysis of covariance revealed that both male and female blue-collar tended to sleep for significantly shorter durations than those in the other occupations. The results of the current study indicate that sleep duration is affected by occupation. When determining the cause of loss of sleep, medical personnel should consider their patient's lifestyles and how they have been affected by their occupation.